Clima motivacional en el equipo de futsal de la Universidad Antonio Nariño (2024)
The present research was conducted with the objective of identifying the motivational climate present in the futsal team of the Antonio Nariño University in order to describe and analyze the factors associated with the different dimensions that comprise the task and ego climate. Therefore, it was considered pertinent to approach this research from a descriptive quantitative approach using the questionnaire (PMCSQ-2) Newton, Duda, and Yin (2000).